Pengaruh Fly Ash dan Abu Vulkanik Sebagai Penambah Semen Terhadap Kuat Tekan Paving Berpori - Afrianto, Arif; Wibowo, Rendi Gusta; Cahyono, Ari (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Porous paving is a type of paving that allows water from rainfall or other sources to seep through the paving, which can reduce runoff from a location and increase groundwater recharge. In this study, porous paving uses coarse aggregates measuring 5-10 mm, a water-cement factor of 0.4% and the addition of coal fly ash and volcanic ash. Testing includes density, water absorption, and compressive strength of porous paving with a mixture composition of coal fly ash and volcanic ash of 0%, 2.5%, 5%, 7.5% and 10% tested at 28 days with 30 test objects. For the ratio of cement and coarse aggregate 1:4. The best compressive strength results were obtained by adding fly ash and volcanic ash 2.5%, namely 182,500 kg/cm2, 0% = 182,000 kg/cm2, 5% = 181,667 kg/cm2, 7.5% = 181,167 kg/cm2, and 10% = 180,667 kg/cm2. The smallest porosity Addition of fly ash and volcanic ash 2.5% = 1.47%, addition of 0% = 1.55%, 5% = 1.94%, 7.5% = 2.33% and 10% = 2.35%. The highest density when adding fly ash and volcanic ash is 2.5% = 1.04 gr/cm3, 5% = 1.03 gr/cm3, 7.5% = 1.03 gr/cm3, 0% = 1.03 gr/cm3 and 10% = 1.02 gr/cm3.